Introduction to the 4.0 Education Revolution for Counseling Guidance Teachers - Rufman Iman Akbar (STMIK Pontianak, 2023)
This community service activity is carried out to provide teachers with an understanding and ability to face the education era 4.0. Training is carried out by combining assignments, discussions, and reflections. The results can increase the knowledge and capacity of the teachers involved in the activity. The increase occurred quite significantly, based on the assessment that has been done. This service is carried out to provide increased understanding and ability in terms of developing constructivist concepts. From the evaluation results, further training is needed regarding the teacher's ability to utilize technology in learning, implement class changes, and use MOOCs in education. Furthermore, this training can also be carried out so that teachers can be more prepared to accept the changes in this educational revolution..